The Interpretation Provisions in the New Zealand Income Tax Act 1994 - Prebble, John (Victoria University of Wellington Law Review, 1999)
Historically, courts have been unwilling to adopt a purposive approach to the interpretation of tax statutes. This reluctance extends to the application of section 5(j) of the Acts Interpretation Act 1924, which courts say has no general applicability to income tax legislation. In 1996, as part of a process of rewriting the Income Tax Act 1994, Parliament inserted a number of interpretation provisions into the Act. The goal that the drafters had in mind is not entirely clear, but the 1996 interpretation provisions appear to be calculated to require the courts to interpret the Act more purposively, meaning, in this context, to interpret the Act more in the light of the overall objective of levying tax. If that was indeed the goal, the 1996 provisions do not achieve it, nor is it possible to determine whether the provisions achieve other worthwhile goals. Indeed, the stipulation in section AA 3(1) that provisions of the Act should be interpreted "in [the] light of the purpose provisions, the core provisions, and the way in which the Act is organised" may in future be turned against the interests of the Crown in order to support otherwise unpersuasive arguments on behalf of taxpayers.